Impact of congenital heart disease on outcomes of pediatric heart‐lung transplantation. (30th December 2013) - Keeshan, Britton C.; Goldfarb, Samuel B.; Lin, Kimberly Y.; Kreindler, James L.; Kaufman, Beth D.; Gaynor, James W.; Shaddy, Robert E.; Rossano, Joseph W.
Abstract HLT is reserved for children with cardiopulmonary disease not amendable to alternative therapies. Children with CHD with or without ES may be considered for HLT. Outcomes of HLT in this population are not well described. To test the hypothesis that CHD without ES is associated with worse graft survival and identify factors associated with poor outcome, a retrospective analysis of the UNOS database was performed. One hundred and seventy‐eight pediatric HLTs were performed between 1987 and 2011. CHD was the diagnosis in 65 patients, of which 34 had CHD without ES. Patients with CHD without ES had decreased patient survival (median 1.31 yr) compared with CHD with ES (4.80 yr, p = 0.05). On multivariable analysis, the following were associated with graft failure: CHD without ES (adjusted HR 1.69, 95% CI 1.09–2.62), younger age (1.04, 1.01–1.08), pretransplant mechanical ventilation (1.75, 1.01–3.06), pretransplant ECMO (3.07, 1.32–7.12), pretransplant PRAs (1.53, 1.06–2.20), and transplant era (1.85, 1.16–2.94). In children with CHD who require HLT, underlying physiology influences outcomes. Those without ES have a worse prognosis. The diagnosis of CHD without ES and preoperative factors may inform decisions in a complex patient population.